Deregulation of SYCP2 predicts early stage human papillomavirus‐positive oropharyngeal carcinoma: A prospective whole transcriptome analysis. Issue 11 (16th October 2015) - Masterson, Liam; Sorgeloos, Frederic; Winder, David; Lechner, Matt; Marker, Alison; Malhotra, Shalini; Sudhoff, Holger; Jani, Piyush; Goon, Peter; Sterling, Jane
Abstract : This study was designed to identify significant differences in gene expression profiles of human papillomavirus (HPV)‐positive and HPV‐negative oropharyngeal squamous cell carcinomas (OPSCC) and to better understand the functional and biological effects of HPV infection in the premalignant pathway. Twenty‐four consecutive patients with locally advanced primary OPSCC were included in a prospective clinical trial. Fresh tissue samples (tumor vs . matched normal epithelium) were subjected to whole transcriptome analysis and the results validated on the same cohort with RT–quantitative real‐time PCR. In a separate retrospective cohort of 27 OPSCC patients, laser capture microdissection of formalin‐fixed, paraffin‐embedded tissue allowed RNA extraction from adjacent regions of normal epithelium, carcinoma in situ (premalignant) and invasive SCC tissue. The majority of patients showed evidence of high‐risk HPV16 positivity (80.4%). Predictable fold changes of RNA expression in HPV‐associated disease included multiple transcripts within the p53 oncogenic pathway (e.g. CDKN2A / CCND1 ). Other candidate transcripts found to have altered levels of expression in this study have not previously been established ( SFRP1, CRCT1, DLG2, SYCP2, and CRNN ). Of these, SYCP2 showed the most consistent fold change from baseline in premalignant tissue; aberrant expression of this protein may contribute to genetic instability during HPV‐associated cancer development. If further corroborated, this data may contribute to the development of a non‐invasive screening tool. This study is registered with the UK Clinical Research Network (ref.: 11945). Abstract : This study was designed to identify significant differences in the gene expression profiles of HPV‐positive and HPV‐negative oropharyngeal squamous cell carcinomas (OPSCC). Our objective was to better understand the functional and biological effects of HPV infection in the pre‐malignant pathway.